Power Component of Russian Policy in the Mirror of Geoeconomics - E F Chernenko (Vestnik RUDN. International Relations, 2012)
Power component of geoeconomics is under consideration in the article. Specific features of Russian power strategy, power policy and power diplomacy are discussed in the context of national interests and security.